2008
DOI: 10.1152/ajprenal.00075.2008
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of NEPH1 from nephrin is involved in development of a rat model of focal segmental glomerulosclerosis

Abstract: Focal segmental glomerulosclerosis (FSGS) is a disease showing severe proteinuria, and the disease progresses to end-stage kidney failure in many cases. However, the pathogenic mechanism of FSGS is not well understood. The slit diaphragm (SD), which bridges the neighboring foot processes of glomerular epithelial cells, is understood to function as a barrier of the glomerular capillary wall. To investigate the role of SD dysfunction in the development of FSGS, we analyzed the expression of SD-associated molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 52 publications
3
45
0
Order By: Relevance
“…33,37 Mutations disrupting the raft localization of podocin or the nephrin/podocin interaction disassociate nephrin from the raft-mediated trafficking pathway, disrupt its membrane localization, and cause congenital proteinuria. 33,38 We found that INF2 interacts with podocin and caveolin-1, proteins both involved in lipid raftmediated trafficking; this finding suggests a direct role for INF2 in lipid raft-mediated SD protein trafficking. In addition to podocin and caveolin-1, recent studies have also identified INF2's association with raft proteins MAL and MAL2, which mediate membrane trafficking of functional molecules in Schwann cells, 24 T lymphocytes, 39 Madin-Darby canine kidney cells, and HepG2 hepatocytes.…”
Section: Discussionmentioning
confidence: 68%
“…33,37 Mutations disrupting the raft localization of podocin or the nephrin/podocin interaction disassociate nephrin from the raft-mediated trafficking pathway, disrupt its membrane localization, and cause congenital proteinuria. 33,38 We found that INF2 interacts with podocin and caveolin-1, proteins both involved in lipid raftmediated trafficking; this finding suggests a direct role for INF2 in lipid raft-mediated SD protein trafficking. In addition to podocin and caveolin-1, recent studies have also identified INF2's association with raft proteins MAL and MAL2, which mediate membrane trafficking of functional molecules in Schwann cells, 24 T lymphocytes, 39 Madin-Darby canine kidney cells, and HepG2 hepatocytes.…”
Section: Discussionmentioning
confidence: 68%
“…Our previous study suggested that in addition to Neph1 phosphorylation, the extracellular engagement of Neph1 also induces its internalization and subsequent downstream signaling from the cytoplasmic domain of Neph1 (12,42). This led us to hypothesize that selectively targeting the cytoplasmic domain of Neph1 will affect Neph1 phosphorylation and its ability to internalize.…”
Section: Discussionmentioning
confidence: 99%
“…Retained Its Functionality-We have previously shown that the extracellular engagement of Neph1 induces its activation that includes Neph1 phosphorylation, its internalization, and subsequent downstream signaling mediated by the cytoplasmic domain of Neph1 (12,42). Therefore, we hypothesized that if we selectively target the cytoplasmic domain of Neph1 by competitive inhibition, it may result in the inhibition of Neph1 phosphorylation and therefore Neph1 internalization.…”
Section: Tat-neph1cd Was Transduced In Podocytes Where Itmentioning
confidence: 99%
“…[33,34]. The dissociation of Neph1 from Nephrin induced proteinuria in FSGS [35]. The Neph1-Nephrin complex cooperate to induce actin filament nucleation and elongation in a tyrosine phosphorylation dependent fashion at the plasma membrane by recruiting the cytoskeletal adaptor protein Nck1/2 and other proteins of the actin polymerization complex [36,37].…”
Section: Neph Proteinsmentioning
confidence: 99%